Autoclictic behavior: Systematic review of experimental studies (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Literature reviews about verbal behavior often indicate that there are few experimental studies about autoclitic behavior. However, there may be experimental studies of a behavioral analytical character that address autoclitics without using this term. This article performed a literature review seeking (1) to expand the knowledge about behavioral analytical experimental studies that address autoclitics, and (2) to describe and analyze participants’ profile, teaching procedures used, evaluated autoclitics and main results of the studies. The search was carried out in the CAPES scientific journal portal using the terms 'autoclitic', 'behavior analysis', and terms related to grammar. Thirty-seven (37) articles were selected that investigated autoclitic, 24 of which did not use the term. Most study participants were children with atypical development, relational autoclitics were the most studied and the multiple exemplar training and instruction proved to be important to teach autoclitics. Based on these results, new research questions are suggested.
Keywords: Verbal behavior; autoclitic; grammar; multiple exemplar instruction; multiple exemplar training